A study for the efficacy of Amr’s cervical traction maneuver along with AMTSL in prevention of postpartum hemorrhage - Rani, Rekha; Golani, Monica; Singh , Shikha; Urvashi; Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Postpartum hemorrhage (PPH) contributes to 25% maternal mortality worldwide (WHO, 2007). In poor resource settings where facility of refrigeration is not available uterotonics may not prove to be useful in prevention of PPH. The aim of this study is to find out the efficacy and acceptability of Amr’s cervical traction maneuver in prevention of PPH in such set up. Methods: This interventional observational study was conducted among 220 patients coming in labour eligible for vaginal delivery in Department of Obstetrics and Gynaecology, S. N. Medical College, Agra between December 2020 to May 2022. Patients were divided into two groups: study group (110 patients) where Amr’s maneuver along with AMTSL is done and control group: where AMTSL is done alone. Results: The mean age of participants in study group was 23.76 years and control group was 23.75 years. In both groups, 59.5% were primigravidae. Mean BMI in both group was 25.02 kg/m2. Almost 61% had spontaneous labour. Nearly 92% delivered normally without instruments. In study group 66% patients had blood loss less than 400ml. Average blood loss was 255.23 ml in study group and 300.25 ml in control group. The difference is clinically significant. The mean blood loss in PPH patients in study group was 603.75 ml, and in control group it is 753.25 ml, which is clinically significant. Conclusions: Amr’s maneuver is a simple maneuver when done in combination with AMTSL results in reducing the incidence of PPH and amount of blood loss post-delivery to a great extent.